(untitled) (BIRDEM Medical Journal, 2022)
Background: The incidence of diabetes mellitus is on a constant rise, affecting children and the elderly alike. This incidence is presumed to rise even further in the next few decades. Diabetes is often associated with various cardiovascular and kidney-related comorbidities, which can greatly affect the life expectancy. The comorbidities often have a direct influence on the mortality rate. The present study was conducted to find out the cause of death among hospitalized diabetic patients. Methods:This retrospective study was conducted Medicine and allied departments of BIRDEM General Hospital, Dhaka, Bangladesh. The study period was July 2020 to June 2021 and the study was conducted with the data of 75 patients. Data was collected from hospital records by retrieving the files with proper permission from hospital authority. Patients whose cause of death was due to traumatic injury unrelated to diabetes and cases where investigation reports were not available were excluded from the study. Ethical approval was obtained from the ethical review committee of Bangladesh Diabetic Association. Results:Among the study subjects, 38.7% were older than 70 years, 30.7% between 61-70 years and only 4% between 23-40 years. Mean age was 65.3±13.2 years. There was slight male predominance, with male: female ratio 1.3:1. Clinical presentation included fever (60%)and shortness of breath (49.3%). Hypertension was the most common comorbidity (92%), followed by chronic obstructive pulmonary disease (18.7%) and acute kidney injury on chronic kidney disease (37.3%). The most common cause of death was urosepsis (30.7%) followed by septic shock (13.3%), myocardial infarction (12%) and the least common cause was meningoencephalitis (1.3%). Conclusion: The study found that the most common cause of death in diabetic patients was sepsis, specifically urosepsis, followed by renal failure and cardiovascular disease related ailments. BIRDEM Med J 2022; 12(3): 212-216